THE IMPACTS OF HIV AIDS ON FAMILIES AND COMMUNITIES IN ALBANIA - Zeka, Xhevdet; Gjergji, Elda; Hodaj, Monika (European Scientific Journal, ESJ, 2012)
﻿Since HIV was first identified in 1983, over 65 million people have been infected, of whom 25 million have died. In the past 20 years HIV/AIDS has become an increasing global phenomenon. In countries hard hit by the pandemic, morbidity and mortality have risen and are expected to continue to rise. The implications of rising morbidity and mortality are not only that HIV/AIDS is changing the demographic structure of the household but also that it is taking a heavy toll on the socio-economic well-being of households and communities. These socio-economic effects are largely borne by individuals, households, and communities with little, if any, support from the technology change community and policy maker. This paper will discuss the ways in which HIV/AIDS could potentially devastate governments, economies, relationships between younger and older population and the other parts of society. It will also identify political and social challenges faced by the global effort fighting the HIV/AIDS epidemic. The study made use of secondary data sources, supplemented by survey of a selected group of Albanians who are engaged in AIDS’ research and relief issues. Findings revealed that AIDS has had a major impact on the relationships between the younger and older populations in the affected areas in Albania. It has considerably increased the caregiving responsibilities and challenges faced by the older population at the time when they are supposed to be receiving care. AIDS caregivers face discrimination as a result of the stigma attached to the disease. Governmental policies and programs have not been adequate in addressing the intergenerational challenges that arise as a result of the disease. Recommendations are made as a way to tackle the challenges.